2010
DOI: 10.1371/journal.ppat.1000853
|View full text |Cite
|
Sign up to set email alerts
|

Three Members of the 6-cys Protein Family of Plasmodium Play a Role in Gamete Fertility

Abstract: The process of fertilization is critically dependent on the mutual recognition of gametes and in Plasmodium, the male gamete surface protein P48/45 is vital to this process. This protein belongs to a family of 10 structurally related proteins, the so called 6-cys family. To identify the role of additional members of this family in Plasmodium fertilisation, we performed genetic and functional analysis on the five members of the 6-cys family that are transcribed during the gametocyte stage of P. berghei. This an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
265
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(273 citation statements)
references
References 74 publications
(166 reference statements)
8
265
0
Order By: Relevance
“…Studies of rodent malaria P. berghei have indicated that HAP2 is localized on male gametocytes and microgametes (251) and that HAP2 is not necessary for adhesion of gametes but is essential for the fusion of gamete surface membranes (251). P48/45 belongs to a family of proteins that are characterized by six positionally conserved cysteines (6-Cys proteins) (494). All 6-Cys proteins contain a signal peptide, and most contain a putative glycosylphosphatidylinositol (GPI) anchor sequence, making it plausible that they are located on the surfaces of parasites or invasion-associated organelles (473,498).…”
Section: Immune Responses Influencing Gametocyte Infectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of rodent malaria P. berghei have indicated that HAP2 is localized on male gametocytes and microgametes (251) and that HAP2 is not necessary for adhesion of gametes but is essential for the fusion of gamete surface membranes (251). P48/45 belongs to a family of proteins that are characterized by six positionally conserved cysteines (6-Cys proteins) (494). All 6-Cys proteins contain a signal peptide, and most contain a putative glycosylphosphatidylinositol (GPI) anchor sequence, making it plausible that they are located on the surfaces of parasites or invasion-associated organelles (473,498).…”
Section: Immune Responses Influencing Gametocyte Infectivitymentioning
confidence: 99%
“…P48/45 is essential for the attachment of male microgametes to fertile female macrogametes in P. berghei (493). In addition to the Pfs48/45 gene, two more 6-Cys protein genes are expressed exclusively on P. falciparum gametes (Pfs47 and Pfs230 genes), suggesting a role in gamete recognition and fertilization (228,494,498,499,515). Pfs47 is a female-specific paralogue of Pfs48/45 located on the surfaces of female gametes following their emergence from erythrocytes, but it does not appear to be crucial for fertilization (498).…”
Section: Immune Responses Influencing Gametocyte Infectivitymentioning
confidence: 99%
“…Numerous Plasmodium surface proteins are highly polymorphic (46 -50), including a majority of the 6-Cys proteins (4,19,(51)(52)(53). To determine the evolutionary selection pressures acting on individual 6-Cys protein family members, we analyzed synonymous (dN) and non-synonymous (dS) polymorphisms among P. falciparum isolates to estimate the dN/dS ratio , which measures the strength of selection acting on a proteincoding gene, for Pf12, Pf38, Pf41, Pfs47, Pfs48/45, Pf52, Pf92, and Pfs230 (Fig.…”
Section: Purifying Selection and Apical Localization Of Pf12 Suggest Anmentioning
confidence: 99%
“…Pfs230 is a 360-kDa protein that contains 7 CM domains ( Fig. 1A) (6,11,36) and elicits a humoral immune response in infected individuals that can mediate transmission-blocking immunity (12,16). Consequently, Pfs230 as a component of a vaccine offers the advantage that it will elicit an immune response that is boosted by natural infection and will thus provide long-lasting immunity (3,28).…”
mentioning
confidence: 99%